STUDY OF THE PHYSICAL PROPERTIES OF WET NOODLES WITH ADDITION OF SEA WEED - Billina, Aisya (The University of Lampung, 2015)
The objective of this research was to study the physical properties ofwet noodles with addition of sea weed suchas: water content, water absorption, expand ability, strength of noodles, as well as color. This research wasconducted at6 different compositions as treatmentwith 3 replications for each treatment. Wetnoodleswasmadeas many as 6 treatments using 1kg of flour pertreatment, with100% of of wheat flour (control) and five othertreatments is by adding sea weed with a ratio of 15%, 20%, 25%, 30%and 35%by weight of wheat flour. Theresults showthat thewet noodleproduced has amoisture content ranging from35,18%to 35,75%for dryandwetnoodle 52,10% to 52,85% for wet noodles cooked, power development wet noodle sranged between 25,71%to33,06%, water absorption 55,80% to 60,36%, breaking noodle power ranging from 5 N to 5,67 N and wetnoodle color significantly in each treatment.Keywords: physical properties, seaweed,wet noodles, wheat flour.